Implementation of Tourism Promotion Project (TPP) concepts based on local needs to increase students’ speaking skill - Jumrah (International Journal of Humanities and Innovation (IJHI), 2018)
This study aims to determine whether the implementation of the Tourism Promotion Project Concept (TPP) based on local needs could improve students’ speaking skill. This study uses Classroom Action Research. The implementation of the action consists of 2 (two) cycles in which cycle I consist of the planning, implementation, observation, and reflection, while cycle II is the improvement steps from the implementation of action in cycle I. Observation, speaking test, documentation and research note are used as an instrument of this research. The results showed that by using the TPP concept based on local needs, students' speaking skill in English Department academic year 2016/2017 increased from 2 cycles run with two meetings in each cycle. This is seen in the percentage of student success. In the first meeting of the cycle I, only one student is in the excellent category. Then in the second meeting of the same cycle, there are three students in excellent category, and just only one student is in the poor category. While in the first meeting of the second cycle, the number of students in excellent category increased to 13 students and there are no students in the poor category. In the second meeting of cycle II, the number of students in excellent category increased to 25 students, and there are no students in two bottom category (insufficient and poor category).